Understanding the Sustainability of Insurgency Conflict in Thailand. (1st July 2013) - Manmuang, Sanakorn; Yolles, Maurice; Talabgaew, Sompoap
Abstract : This article seeks to model the insurgency conflict in the three southern border provinces of the Kingdom of Thailand: Pattani, Yala, and Narathiwat. In so doing, it will explore the sustainability of the conflict by representing it in terms of a conflict life cycle that is responsive to complexity and change. The cycle arises from the cybernetic viable systems theory of 'living systems', and is able to foster a better understanding of what is happening empirically on the social level in these provinces, in respect to a situation characterized as one of incessant conflicts. This conflict model that arises suggests that there is an interconnection between the agents involved, and their individual and interactive dynamics. The conflict involves five types of politically related behaviours that occur between two interactive agents: the state (engaged in searching for and making arrests of insurgents) and the insurgents (engaged in violent acts of shooting, bombing, and arson). These agents are studied to the end of being able to determine the precise interactive nature of the political conflict in which they are engaged. In carrying out this investigation both quantitative and qualitative approaches were used. The research was carried out in three stages. In the first stage, time series techniques were used to determine inferentially whether the conflict is both rational and involves interactive behaviours. Stage two adopts the Weibull distribution technique to assess the political conflict. In the third stage, a statistical analysis is conducted of the conflict situation in political terms. Finally, it is explained how the model and the methods used in this article may be used to deal with intractable conflict in other social environments, incidentally tracking the likelihood of conflicts being sustainable. Other agencies could utilize this approach in examining other political conflicts so as to be better able to prepare suitable approaches for coping with intractable conflicts to the end of fostering sustainable peace processes.